Racial profiling [ research, racism, and resistance - Glover, Karen S. , 1964- (Issues in crime & justice, 2009)
This book is a critical examination of mainstream research on racial profiling. Through qualitative analysis of interviews with people of color who have experienced racial profiling, it offers an alternative understanding of racialized law and the traffic stop as the manifestation of racialized law enforcement.